Features of the financial services for diagnosis - Olena Golovko; G. S. Gluhoded (Фінансово-кредитна діяльність: проблеми теорії та практики, 2014)
Considering concept of diagnostic tasks principles and algorithm how it realization. Рroposed of mechanism for financial diagnostics company.